An evaluation of employment creation and skills transfer during the delivery of capital projects in Sub-Saharan Africa: a focus on three selected case studies - Mwamlima, Bwinghane Tusubile (My University, 2017)
Large-scale strategic ventures to build, add or improve an asset are being delivered in different sectors of industries around the world. These ventures resort to the intensive use of capital and resources and are mostly referred to as “capital projects”. Because of the large-scale nature of these capital projects, they have profound effects on their host countries, and their impact is larger than simply client and turnover, thereby influencing different areas of surrounding society. The nature and extent of this impact are (i) environmental, (ii) political, (iii) socio-economic and (iv) cultural. Amongst the socio-economic objectives is the capability to provide on-the-job training and create more job opportunities than would otherwise be possible. Recently there has been a surge of these capital projects in sub-Saharan Africa. However, sub-Saharan Africa continues to experience high levels of unemployment and a lack of skillsets. In an attempt to help address these problems, this research project evaluates employment creation and skills transfer during the delivery of capital projects in sub-Saharan Africa. Three case studies (researched between October 2013 and February 2015) were selected to collect data for this research project: (1) Nacala Corridor Railway Project (Malawi), (2) the Medupi Power Project (Republic of South Africa) and (3) the Gautrain Project Phases 1 and 2 (Republic of South Africa). The research findings illustrate clearly that there has been a significant positive shift in the creation of employment and skills transfer on capital projects. However, there are areas of weakness which have been identified even though the three case studies produced different results. In conclusion, the main weaknesses identified in all three projects are the lack of local high-level skilled employees and a clear indication that these capital projects are not being capitalised efficiently to develop skills amongst the locals, which are essential for such projects. Recommendations are provided for the sustainability of skills development and employment creation on capital projects.
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Science in Engineering to the Graduate School of Engineering and the Built Environment of the Faculty of Engineering and the Built Environment University of Witwatersrand, Johannesburg March 2017
Keywords: Economic development projects--Africa, Sub-Saharan; Job creation--Africa, Sub-Saharan; Capital investments--Evaluation; Project management--Africa, Sub-Saharan